METHODS OF REGULATION OF MONEY TURNOVER STABILIZATION (World Economics and Finance Bulletin, 2022)
The article presents methods of regulation and stabilization of money circulation, money circulation, market economy, as well as purchasing power
Keywords: monetary circulation; inflation; method; money